Impact of Nasal Surgery on Speech Resonance. (August 2014) - Brandt, Michael G.; Rotenberg, Brian W.; Moore, Corey C.; Bornbaum, Catherine C.; Dzioba, Agnieszka; Glicksman, Jordan T.; Doyle, Philip C.
Objectives: The nose and paranasal sinuses contribute to speech resonance and changes to these structures may alter speech nasality. This change may influence one's vocational and social functioning and quality of life. Our investigation explored objective and subjective changes in nasality following nasal surgery in a prospective and longitudinal fashion. Methods: Recordings of sustained vowel and sentence stimuli and voice-related quality of life measurements were obtained preoperatively and at 2, 4, 8, and 24 weeks postoperatively from individuals undergoing nasal and/or sinus surgery. Objective measures of fundamental frequency, jitter, shimmer, and harmonic to noise ratio (HNR) were determined. Pre- and postoperative speech samples were assessed by 15 naïve listeners. Results: In all, 15 subjects completed the study. Neither speakers nor listeners perceived a subjective change in nasality following surgery. No statistically significant change in microacoustic measures were identified. Although nasal sentences did not reveal differences for 3 microacoustic measures, a difference in HNR was identified. Conclusions: Patients undergoing nasal surgery did not exhibit subjective changes in resonance postoperatively. Aside from a difference in HNR for the nasal sentence, objective microacoustics remained unchanged. These results demonstrate the stability of oranasal resonance despite nasal surgery and provide valuable data for patient informed decision-making.